Tramadol for the treatment of cancer pain: Case report - Önal, S. Ates; Yildirim, A. (My University, 2002)
The treatment algorithym for cancer pain is the analgesic ladder that is determined by the World Health Organization (WHO) 20 years ago. Tramadol is a weak opioid analgesic that is administered at the 2nd step of the analgesic ladder. Safe and effective analgesia is obtained with tramadol without reaching high doses, in a patient with multiple primary cancer origins, multiple metastasis and severe systemic infection. The case is discussed under the view of literature.
Kanser a?risinda tramadol: Olgu sunumu
Keywords: Analgesia; Cancer pain; Tramadol